Serum resolvin D1 levels as a marker of inflammation in constipation dominant irritable bowel syndrome - Karatay, Eylem; Utku, Özlem Gül (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The objective of this study is to determine the role of circulating resolvin D1 (RvD1) in patients with constipation subtype of irritable bowel syndrome (IBS-C) and evaluate the relationship between abdominal pain severity and RvD1 levels. Materials and Methods: This research included 55 patients with IBS-C and 36 healthy controls. Controls were selected from patients who applied to our department with similar complaints as IBS but were not diagnosed with any type of pathology after further investigations. All participants underwent complete blood count, C-reactive protein (CRP), and RvD1 levels measurements. We also recorded abdominal pain severity and the number of bowel movements. Patients with IBS-C were compared with respect to the demographic features and laboratory measurements. Results: The median CRP concentration in patients with IBS-C was significantly higher than that of controls (p=0.003). However, the median RvD1 concentration was significantly lower in the IBS group than that of the control group (p<0.001). The receiver operating characteristic curve analyses revealed that RvD1 concentration lower than 0.47 ng/mL and CRP concentration higher than 3.40 mg/L may identify patients with IBS-C with a high specificity. In the IBS group, there was a strong negative correlation between abdominal pain severity and RvD1 concentration (r=−0.766, p=0.001). Conclusion: This research demonstrates that patients with IBS-C have higher CRP and lower RvD1 concentrations than healthy controls. Both RvD1 and CRP concentrations predict the presence of IBS-C. Additionally, RvD1 concentrations decreased with the increase in abdominal pain severity. Further research works are needed for investigating the role of the RvD1 analogs in the treatment of IBS.